Psychological Treatments for People With Severe and Enduring Anorexia Nervosa: A Mini Review - Zhu, James; Yang, Yive; Touyz, Stephen; Park, Rebecca; Hay, Phillipa (Frontiers in Psychiatry, 2020)
This Mini-Review presents recent research into evidence for psychological treatments for people with severe and enduring anorexia nervosa (SEAN). Two psychological therapies, specialist supportive clinical management (SSCM), and cognitive behavior therapy for anorexia nervosa (CBT-AN) have limited (one randomized controlled study) evidence of efficacy. Both have had adaptations for SEAN, notably with revision of the primary treatment goal of improved quality of life and full weight recovery a secondary goal. A major issue with existing studies is poor definition of SEAN, and the large deficit in research that has used an agreed definition of SEAN. In particular, it may be problematic to extrapolate from studies of people with either severe and/or enduring but not intractable or “resistant” illness. People with longstanding AN who have not received evidence based care should be offered this with an expectation of recovery. Similarly, people with SEAN may be offered care with judicious mitigation of expectations. In the future, trials should include people with SEAN clearly defined. Trials with a subsample of participants likely to have SEAN, if identified at randomisation, are an opportunity for secondary analyses of such participants. This would widen the evidence base for psychological treatments providing hope for people with this devastating illness. Finally, there is an urgent need not only to strengthen our existing knowledge with studies of sufficient power, but also, fundamentally, to derive novel conceptualizations of what “treatment” involves.